Reducing Disrespect and Abuse of Women During Antenatal Care and Delivery Services at Injibara General Hospital, Northwest Ethiopia: A Pre–Post Interventional Study - Mihret H; Atnafu A; Gebremedhin T; Dellie E (Dove Medical Press, 2020)
Habtamu Mihret,1 Asmamaw Atnafu,2 Tsegaye Gebremedhin,2 Endalkachew Dellie2 1Injibara General Hospital, Awi Zone administration, Amhara National Regional State, Injibara, Ethiopia; 2Department of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Endalkachew DellieDepartment of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar Po. Box 196, University of Gondar, Gondar, EthiopiaEmail endalkd.07@gmail.comIntroduction: Disrespect and abuse during pregnancy and childbirth continue to be a barrier for the utilization and quality of care in maternal health services. This study was therefore aimed at reducing the disrespect and abuse of mothers during antenatal care and delivery services at Injibara general hospital, northwest Ethiopia.Materials and Methods: A pre–post interventional mixed method design was conducted among a total of 738 randomly selected mothers who attended antenatal care and delivery services from November 1, 2018 to May 20, 2019. To collect the data, exit interview using an interviewer-administered structured questionnaire was used. Provision of training, preparation of standard written guidelines and protocols, waiting room construction, availing screening or curtain, equipment, essential drugs and supplies, supportive supervision and mentoring, and staff motivation were the lists of interventions applied to decrease disrespect and abuse. Descriptive statistics and independent t-test were computed. The independanet t-test is used because the study populations at the baseline and endline were different. A p-value of < 0.05 and a mean difference with 95% CI was used to test the significance of the interventions.Results: The study revealed that disrespect and abuse during pregnancy and childbirth decreased from 71.8% at baseline to 15.9% at the end-line with a 55.9% change (mean difference: 0.56, 95% CI: 0.55– 0.57). Alongside, the magnitude on the subscales of disrespect and abuse (physical abuse, non-consented care, non-confidential care, non-dignified care, discrimination and neglected care) was decreased at post-intervention, compared with the baseline.Conclusion: Respectful maternal healthcare after the intervention was significantly improved. The finding suggests that provision of training to healthcare providers, written policies and procedures that describe the responsibilities of healthcare providers in the respectful maternal care process, improving facility infrastructure, availing supplies, regular supportive supervision and mentoring and motivation of high-performance employees have the potential to enhance respectful maternal care. Therefore, incorporating such training into pre-service curricula and in‐service training of healthcare workers may indorse the practice of respectful maternal care.Keywords: disrespect, abuse, pregnancy, delivery, intervention, Ethiopia